Uskonnon ja katsomusten asemat eduskuntapuolueiden poliittisissa ohjelmissa 1999–2019 - Jere Kyyrö (Teologinen julkaisuseura, 2025)
The Positions in Finnish Parliamentary Parties’ Political Platforms on Religions and Worldviews, 1999–2019 — This article uses content analysis to explore the positions in Finnish parliamentary parties’ political platforms (including for general and special elections) on religions and worldviews and to identify differences between the parties. The dominant stance has been that of benevolent neutrality towards religion in general. The Christian Democrats have referred to religions and worldviews the most, emphasizing Christian identity and personal faith. The major parties (National Coalition Party, Center Party, and Social Democrats) have highlighted the Finnish Evangelical Lutheran Church’s role as a social, especially third-sector, actor, which is also the most prominent theme across the platforms studied. The Finns Party has emphasized Christianity as a cultural identity, without explicitly mentioning the Lutheran Church or voicing support for any particular religious group. The Green League, Left Alliance, and Social Democrats have approached religion from a position of neutrality, emphasizing equality of worldviews, but have also criticized the privileged position of the Lutheran Church. This privileged position is supported primarily by welcoming it as a third-sector partner and only secondarily by associating it with Finnish culture.